PPR outbreak in goats: Epidemiological and therapeutic studies - KUMAR, A; SINGH, S V; RANA, R; VAID, R K; MISRI, J; VIHAN, V S (The Indian Journal of Animal Sciences, 2014)
An outbreak of PPR occurred in newly purchased goats (30 males of 5-6 months age and 45 adult females. The disease appeared on 12th day of quarantine. Anorexia, fever diarrhoea; nasal discharge and pneumonia were the constant features of the disease, but buccal lesions, conjunctivitis and corneal opacity were observed only in few cases. The overall morbidity, mortality and case fatality rates were 32.1, 5.3 and 16.6% respectively. Influence of disease on haematological profile revealed anaemia and mild leucopenia. Bacteriological study of nasal and faecal swabs revealed organism indistinguishable to Escherichia spp, Corynebacterium spp. and Staphylococcus spp. Necropsy findings consisted of necrotic and ulcerative lesions on lips, gums, buccal mucosa, pharynx, oesophagus and nasal mucosa. Larynx, trachea and bronchi showed congestion and pulmonary parenchyma revealed consolidation and emphysema. Erosive and haemorrhagic abomasi tis and enteritis, enlargement of spleen and Iymphnodes were mainly observed. Antimicrobial and rehydration therapy showed recovery in 55% animals with enrofloxacin, 25% with trimethoprim sulphadiazine, 20% with ampicillin-cloxacillin combiniation and 20% with cefotaxime-amikacin combination. Overall therapeutic survivability was 85.7% with overall recovery rate of 10 days. Disease was confirmed as PPR by serum neutralization (for Morbilli virus) and PPR specific IC-ELISA test.